Generating functional in classical Hamiltonian mechanics - Zazunov, L.G. (Вопросы атомной науки и техники, 2001)
We give a brief survey of a path-integral formulation of classical Hamiltonian dynamics that means a functional-integral representation of classical transition probabilities. This functional exhibits a hidden BRST and anti-BRST invariance. Therefore a simple expression, in terms of superfields, is received for the generating functional. We extend the results for discrete classical systems to continuum mechanics.